The impact of the technical characteristics of motor vehicles on the efficiency of the company - O.V. Garmash; S.V. Bogdanovich; G.V. Muratbekova; L.M. Malikova (Хабаршысы. Экономика сериясы)
This article explores the issue of vehicle efficiency based on its technical characteristics. The aim of the study is to identify the most important technical parameters affecting the efficiency of road transport. The direction of scientific research was to determine the optimal characteristics of the car to achieve maximum efficiency.